Factors influencing export in bilateral trade: An empirical investigation in the Middle-East context - Souad Sherif; Kamel Fantazy (International Journal of Management, Economics and Social Sciences (IJMESS), 2013)
The purpose of this paper is to examine factors influencing export in bilateral trade in the Middle-East context. The study considers the bilateral trade flows across three Gulf Cooperation Council countries - the Kingdom of Saudi Arabia (KSA), Bahrain (BAH) and Qatar (QAT) - over the last 30 years (1981-2010). The study focuses on the relationships between BAH and QAT, combined as one group, and KSA, which has a relatively larger economic mass and population. Data related to bilateral trade was collected from the International Monetary Fund (IMF). The proposed model was tested using the Structural Equation Modeling (SEM) technique. Our results indicated that GDP, POP_GR, and GDP/CA have a positive relationship with the level of KSA_EX, while the DIST related negatively to the level of KSA_EX. The study shows that all factors are crucial to the success of bilateral trade flow between both parties (BAH and QAT) and KSA because they provide the facts that decision makers need to make the appropriate decisions. Lastly, the article discusses research contributions and limitations of the study that could be addressed in future research scope.
Keywords: F14; F15; 330; bilateral trade; economic integration; structural equation modeling; Gulf Cooperation Council; regional integration